The Division Of Distributable Assets To The Non-Muslim Heirs Based On Compilation Of Islamic Law - Siska Lestari; Danceu Danceu; Sri Endah Wahyuningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Inheritance issues are particularly vulnerable because they are related to total assets to be distributed to the heirs. This issue often occurs and ends up in court, especially concerning the issue of inheritance for non-Muslim heirs. Based on the Compilation of Islamic Laws, non-Muslim heirs are not entitled to the inheritance of the Muslims family. For non-Muslim heirs, this is very unfair, so it can cause disunity within the family. Islam prioritizes justice and prosperity, so that cases of non-Islamic heirs can be given alternative solutions by giving inheritance through a mandatory will (Wasiat Wajibah).Keywords: Inheritance; Non-Moslem Heir; Compilation of Islamic Law.